PELAKSANAAN PEMBELAJARAN DARING DI PRODI PPKn FKIP UNIVERSITAS MATARAM - Fahrurrizal Umam; Bagdawansyah Alqadri; Muhammad Ismail (Jurnal Pendidikan Sosial Keberagaman, 2022)
This study aimed to (1) determine the implementation of online learning at the PPKn Study Program, FKIP, University of Mataram, (2) to find out the supporting and inhibiting factors for the implementation of online learning at the PPKn Study Program, FKIP, University of Mataram, (3) to determine the efforts to overcome the factors that hinder the implementation of online learning at the PPKn Study Program, FKIP, University of Mataram. This research was conducted in the PPKn Study Program, FKIP, University Mataram. The method used in this study is a qualitative approach to determine the symptoms or phenomena related to the implementation of online learning in the PPKn Study Program, FKIP, University of Mataram.  Data collection techniques used are interviews, observation, and documentation. The data analysis technique was carried out with the data reduction stage, the data display stage, and the conclusion drawing stage. The results showed that the implementation of online learning at the PPKn Study Program, FKIP, University of Mataram running well and smoothly. Students and lecturers have electronic tools to support online learning, namely cellphones and laptops that can be connected to the internet network.  Online learning uses a variety of learning methods, such as the lecture method, question and answer, and discussions or group percentages. Then students and lecturers use various kinds of learning media platforms used for lecture activities, namely Google Meet, SPADA.  Zoom Meeting, and Google Class Room.